1980
DOI: 10.1159/000198447
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo </i>Plasma Cholesterol Exchanges in the Digestive Tract of the Rat: Effect of <i>L</i>-Thyroxine

Abstract: Cholesterol exchanges between plasma and digestive organs (stomach, small intestine divided into jejunum and ileum, cecum plus colon) were studied in control and in L-thyroxine-fed rats receiving a constant venous infusion of (3H)-cholesterol for 3 or for 6 h and in unoperated rats by use of the isotopic equilibrium method. In control rats, total cholesterol radioactivity in the walls of stomach, intestine and cecum-colon averaged 0.50% of infused (3H)-cholesterol at the end of 6 h; betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In rats receiving daily subcutaneous injec tions of labelled cholesterol for 1 month, the specific activity of cholesterol is similar in top or villus cells from the duodenum or ileum, and reaches 50-55% of plasma cholesterol-specific activity. This shows that about half of the enterocyte cholesterol has been exchanged with plas ma cholesterol in the course of the cell's life [29,30], Since a similar pattern is noted under those conditions, in the crypt and apical cells, infusion experiments were performed in order to label only plasma cholesterol in bile fistula rats receiving a compensatory infusion of (unla belled) bile. Cholesterol-specific activity in enterocytes was monitored during 3 or 6 h. The distribution of plasma cholesterol in the core villus and in the epithelial cells localized at the different levels of the villus was also observed 6 or 11 h after either an intravenous infusion or a pulse of radiolabelled cholesterol [30], These experi ments demonstrated that the exchanges of plasma choles terol through the epithelial basal membrane are lower than through the capillary membrane, and do not depend on the localization of the epithelial cell on the villus (crypt or apex).…”
Section: Cholesterol Exchanges Between Plasma and Mucosai Cellsmentioning
confidence: 97%
“…In rats receiving daily subcutaneous injec tions of labelled cholesterol for 1 month, the specific activity of cholesterol is similar in top or villus cells from the duodenum or ileum, and reaches 50-55% of plasma cholesterol-specific activity. This shows that about half of the enterocyte cholesterol has been exchanged with plas ma cholesterol in the course of the cell's life [29,30], Since a similar pattern is noted under those conditions, in the crypt and apical cells, infusion experiments were performed in order to label only plasma cholesterol in bile fistula rats receiving a compensatory infusion of (unla belled) bile. Cholesterol-specific activity in enterocytes was monitored during 3 or 6 h. The distribution of plasma cholesterol in the core villus and in the epithelial cells localized at the different levels of the villus was also observed 6 or 11 h after either an intravenous infusion or a pulse of radiolabelled cholesterol [30], These experi ments demonstrated that the exchanges of plasma choles terol through the epithelial basal membrane are lower than through the capillary membrane, and do not depend on the localization of the epithelial cell on the villus (crypt or apex).…”
Section: Cholesterol Exchanges Between Plasma and Mucosai Cellsmentioning
confidence: 97%
“…Moreover, cholesterol is exchanged between the plasma, stomach and caecum-colon. These exchanges are slightly lower than for the intestine (Lutton and Brot-Laroche, 1980). These two processes should lead to a progressive decrease in the radioactivity incorporated into cholesterol after 14 Cacetate injection.…”
Section: Introductionmentioning
confidence: 74%
“…If the model for the turnover of cholesterol synthesized in the intestine is assumed to be an open compartment having 2 outputs, fecal elimination (RE) and transfer into plasma (RI) (fig. 4) (Giraud-D'Hollander et al, 1976 ;Lutton and Brot-Laroche, 1980 (Lutton and Brot-Laroche, 1979). …”
Section: Introductionmentioning
confidence: 99%
“…As it is well established that the lymphatic pathway is the exclusive transport route for cholesterol absorbed and that the metabolism of its molecule (degrada tion of the steroid nucleus by the intestinal microflora included) is very slow, this obser vation could be explained by a transfer of cholesterol molecules between enterocytes and plasma [13]: a part of infused labelled cholesterol, after its uptake from the lumen into the intestinal mucosa would not have been released into the lymphatics but ex changed with plasma cholesterol. Unfortu nately our experimental schedule did not al lowed us to recover it.…”
Section: Discussionmentioning
confidence: 99%
“…The low rates of radioactivity in bile and blood are due to a large dilution of labelled cholesterol with nonlabelled choles terol of the total body, as a simultaneous transfer of cholesterol takes place between the plasma and any tissue [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%